Continuous Renal Replacement Therapy: A Review - Mujahidin; Yasir Teuku; Dzaky. A. N (HM Publisher, 2020)
Kidney is an important organ to maintain hemodynamic stability inside the human body. In patient with acute kidney injury (AKI) there was a decreased kidney function that could interfere hemodynamic stability which can lead to multi organ failure even death. Around 5-10% patients with AKI required renal replacement therapy (RRT) to support their decreased renal function. Continuous renal replacement therapy (CRRT) is one of RRT modality that commonly used for patients with AKI who are hemodynamically unstable or in critically ill conditions.CRRT could divided into 4 mode, slow continuous ultrafiltration (SCUF), continuous veno-venous hemofiltration (CVVH), continuous veno-venous hemodialysis (CVVHD) and continuous veno-venous hemodialfiltration (CVVHDF). CRRT used based on renal and nonrenal indication. Several studies are still trying to prove nonrenal indication of RRT, to ascertain whether CRRT could be used as therapy effectively. Therefore the indication, the mechanism and the comparison of renal replacement therapy are very important to be understood.